Trh práce žen a vliv vybraných politik - Martina Mysíková (Charles University in Prague, Institute of Economic Studies (IES), 2007)
– Employment or, more precisely, participation of women on the labor market is one of the most apparent gender inequalities on the labor market. Economic theories explaining the segregation can be divided into three broader categories: neo-classic and human capital theories, theory of discrimination and finally institutional theory and labor market segmentation theory. The elimination of causes of these inequalities by appropriate policies implementation would help the better use of women working potential and the higher labor market effectivity. There are applied several policies in the Czech Republic which not only does not support the female participation but have rather negative influence. In this study, I investigate the impact of the two policy means, which can negatively influence the labor supply of women in the Czech Republic. First, joint taxation of spouses was enabled. The marginal tax-rate of women increases very often in case of profiting spouses; women might therefore lower their labor supply. Second, the system of the parental leave influences the female participation. The current Czech system can create significant barrier to women in entry and return to the labor market. Therefore, it leads to an excessive loss of the women human capital which markedly lowers their further employability.
Keywords: 330; gender inequality; female participation; neo-classic theory; human capital theory; theory of discrimination; institutional theory; labor market segmentation theory; joint taxation; parental leave; Weibliche Arbeitskräfte; Arbeitsmarktsegmentierung; Geschlechterdiskriminierung; Familienbesteuerung; Elternzeit; Familienpolitik; Tschechische Republik; EU-Staaten